Keefektifan Pembelajaran Bahasa Jepang melalui Video Ditinjau dari Motivasi dan Prestasi Belajar Peserta Didik di SMK Negeri 1 Buer Kabupaten Sumbawa - Wahyu Firwandi (Unversitas Muhammadiyah Mataram, 2022)
Abstract: This study aims to describe: 1) the effectiveness of learning with videos and learning with textbooks and 2) whether learning with videos is more effective than learning with textbooks in terms of students' motivation and achievement in learning Japanese. The population of this study includes all students of class XII SMK Negeri 1 Buer Kab. Sumbawa - NTB which consists of seven classes. A sample of two classes was determined randomly, namely class XII Multimedia (MM) who studied with video and class XII of Computer Network Engineering (TKJ) who studied with textbooks. The instruments used to collect data were a motivational questionnaire to learn Japanese and a Japanese language learning achievement test. To test the effectiveness of learning with videos and learning with textbooks, one sample t test was used at a significance level of 5% and to determine the difference in the effectiveness of learning with videos and learning with textbooks, the Hotelling Trace test (T2) was used at a significance level of 5%, then continued with independent samples t test with Bonferoni criteria at a significance level of 5% to find out which learning media is more effective. The results of this study are as follows: 1) effective video learning in terms of motivation and achievement in learning Japanese, which is indicated by the value of tcount (motivation score) = 7.071 > ttable (0.05;31) = 2.040 and tcount (achievement score) = 33,862 > ttable (0,05;31) = 2,040; 2) learning with textbooks is effective in terms of Japanese language learning achievement, but not effective in terms of motivation to learn Japanese as indicated by the value of tcount (Motivation Score) = 1.223 < ttable(0.05;28) = 2.048 and tcount (Achievement Score) ) = 2.171 > ttable (0.05;28) = 2.048; 3) there is a difference in the effectiveness of learning with videos and learning with textbooks as indicated by the value of Fcount = 11.467 Ftable (0.05; 2; 58) = 3.156 or a probability value of 0.000. Learning with video is more effective than learning with textbooks, which is indicated by the value of tcount (Motivation Score) = 3.885 > ttable (0.025;59) = 2.300 and tcount (Achievement Score) = 2.333 > ttable (0.025;59) = 2.300.Abstrak: Penelitian ini bertujuan untuk mendeskripsikan: 1) efektivitas pembelajaran dengan video dan pembelajaran dengan buku teks dan 2) apakah pembelajaran dengan video lebih efektif dari pada belajar dengan buku teks dalam hal motivasi dan prestasi siswa dalam belajar bahasa Jepang. Populasi penelitian ini meliputi seluruh siswa kelas XII SMK Negeri 1 Buer Kab. Sumbawa – NTB yang terdiri dari tujuh kelas. Sampel dua kelas ditentukan secara acak, yaitu kelas XII Multimedia (MM) yang belajar dengan video dan kelas XII Teknik Jaringan Komputer (TKJ) yang belajar dengan buku teks. Instrumen yang digunakan untuk mengumpulkan data adalah kuesioner motivasi untuk belajar bahasa Jepang dan tes prestasi belajar bahasa Jepang. Untuk menguji keefektifan pembelajaran dengan video dan pembelajaran dengan buku teks, digunakan satu sampel uji t pada tingkat signifikansi 5% dan untuk mengetahui perbedaan efektivitas pembelajaran dengan video dan pembelajaran dengan buku teks, digunakan uji Hotelling Trace (T2) pada tingkat signifikansi 5%, kemudian dilanjutkan dengan uji sampel mandiri t dengan kriteria Bonferoni pada tingkat signifikansi 5% untuk mengetahui media pembelajaran yang mana lebih efektif. Hasil penelitian ini adalah sebagai berikut: 1) pembelajaran video efektif ditinjau dari motivasi dan prestasi belajar bahasa Jepang, yang ditunjukkan dengan nilai thitung (skor motivasi) = 7,071 > ttable (0,05;31) = 2,040 dan thitung (skor prestasi) = 33.862 > ttable (0,05;31) = 2,040; 2) belajar dengan buku teks efektif dalam hal prestasi belajar bahasa Jepang, tetapi tidak efektif dalam hal motivasi belajar bahasa Jepang seperti yang ditunjukkan oleh nilai thitung (Skor Motivasi) = 1,223 < ttable(0,05;28) = 2,048 dan thitung (Skor Prestasi) ) = 2,171 > ttabel (0,05;28) = 2,048; 3) terdapat perbedaan efektivitas pembelajaran dengan video dan pembelajaran dengan buku teks yang ditunjukkan dengan nilai Fcount = 11,467 Ftable (0,05; 2; 58) = 3,156 atau nilai probabilitas 0,000. Pembelajaran dengan video lebih efektif dibandingkan pembelajaran dengan buku teks, yang ditunjukkan dengan nilai thitung (Skor Motivasi) = 3,885 > ttabel (0,025;59) = 2,300 dan thitung (Skor Prestasi) = 2,333 > ttabel (0,025;59) = 2,300